A Novel Secretory Vesicle from Deer Antlerogenic Mesenchymal Stem Cell-Conditioned Media (DaMSC-CM) Promotes Tissue Regeneration - Minkoo Seo; Jin-Chul Kim; Hyung-Ki Kim; Eun wook Choi; Suyeong Jeong; Ki Chang Nam; Mihue Jang (Stem Cells International)
Multipotent stem cells have the capacity to generate terminally differentiated cell types of each lineage; thus, they have great therapeutic potential for a wide variety of diseases. The most widely available stem cells are derived from human tissues, and their use for therapeutic application is limited by their high cost and low productivity. Herein, we report that conditioned media of mesenchymal stem cells (MSCs) isolated from deer antlers enhanced tissue regeneration through paracrine action via a combination of secreted growth factors and cytokines. Notably, DaMSC-conditioned media (DaMSC-CM) enhanced hair regeneration by activating the Wnt signaling pathway. In addition, DaMSC-CM had regenerative potential in damaged skin tissue through induction of skin regeneration-related genes. Remarkably, we identified round vesicles derived from DaMSC-CM, with an average diameter of ~120 nm that were associated with hair follicle formation, suggesting that secretory vesicles may act as paracrine mediators for modulation of local cellular responses. In addition, these secretory vesicles could regulate the expression of Wnt-3a, Wnt-10b, and lymphoid enhancer-binding factor-1 (LEF-1), which are related to tissue renewal. Thus, our findings demonstrate that the use of DaMSC-CM as a unique natural model for rapid and complete tissue regeneration has possible application for therapeutic development.